2005
DOI: 10.1007/s00441-005-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of keratins and analysis of their expression in carp and goldfish: comparison with the zebrafish and trout keratin catalog

Abstract: With more than 50 genes in human, keratins make up a large gene family, but the evolutionary pressure leading to their diversity remains largely unclear. Nevertheless, this diversity offers a means to examine the evolutionary relationships among organisms that express keratins. Here, we report the analysis of keratins expressed in two cyprinid fishes, goldfish and carp, by two-dimensional polyacrylamide gel electrophoresis, complementary keratin blot binding assay, and immunoblotting. We further explore the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…2a"). It showed a positive reaction with the anti-trout-keratin antiserum GPpoly (data not shown), which we previously introduced as a general keratin marker in fish [8,10-15,19]. The two-dimensional position of this protein spot fits the theoretical values calculated from the sequence of AbaK14 (see above and Table 1).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…2a"). It showed a positive reaction with the anti-trout-keratin antiserum GPpoly (data not shown), which we previously introduced as a general keratin marker in fish [8,10-15,19]. The two-dimensional position of this protein spot fits the theoretical values calculated from the sequence of AbaK14 (see above and Table 1).…”
Section: Resultssupporting
confidence: 68%
“…Compared to our recent analyses [14-18,28], we have now included additional type I keratin sequences from zebrafish and Xenopus ; therefore, in this study the K18 branch shows a more complex branching pattern, not allowing a clear identification of the authentic K18 counterparts in the different vertebrates solely on the basis of their position in the tree. However, our previous identification of K18 in shark, bichir, sturgeon, trout and zebrafish was additionally based on its typical occurrence in simple epithelia, such as liver hepatocytes or intestinal mucosal epithelium, corresponding to the situation in man and other tetrapods [10,12-16,19,29]. Nevertheless, these "functional K18 counterparts" identified in the different vertebrate groups have to be considered as paralogous protein sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Club cells containing similarly packed filaments have also been described for the skin of a variety of teleost fish, including cyprinids, catfish, eels and morays [52][53][54]. Our investigations of keratins in carp showed that the club cells (Leydig cells) in this fish are intensively stained by several, monoclonal, keratin-specific antibodies, including antibody 164.4 [22]. But, evidence for thread-like structures similar to those detected in the hagfish gland thread cells is currently not available for any other fish species.…”
Section: Expression Of Tkα and Tkγ In Lamprey Zebrafish And Xenopusmentioning
confidence: 78%
“…Type I and II keratins have so far been found in all classes of vertebrates [10]. Our surveys of keratin expression in lower vertebrates, notably lamprey, shark, trout, zebrafish, carp, goldfish and lungfish, showed that vertebrates generally express at least two different subsets of keratins: one typical for the single-layered, internal epithelia ("S" keratins) and a second typical for the stratified, external epithelia ("E" keratins) [10][11][12][13][14][15][16][17][18][19][20][21][22]. The phylogenetic analyses of the available "E" and "S" keratin sequences so far suggest that the typical "S" keratins K8 and K18 are the only keratins present in all classes of vertebrates.…”
Section: Introductionmentioning
confidence: 99%